The Relationship Between Family, School, and Community Learning Environments and Student Learning Achievement in Elementary School - Syauqi Musfirah Daud Pisba; Fatimah Azzahra; Putri Nadina Shafira Islamy; Irvan Trisno Susandi; Hendardi Rizaldi; Mulki Siregar (Journal of Islamic Education Students (JIES), 2026)
Student learning achievement is influenced by multiple educational environments, yet previous studies have mostly examined family, school, and community environments separately. Evidence regarding their simultaneous relationships with elementary students' learning achievement remains limited. This study aimed to examine the relationships between family, school, and community environments and students' learning achievement at SDN Batu Ampar 10 PG. A quantitative cross-sectional survey was conducted with 67 students selected through simple random sampling. Data were collected using four-point Likert-scale questionnaires and analyzed using validity and reliability tests, classical assumption tests, multiple linear regression, t-tests, F-test, and the coefficient of determination (R²) in SPSS. The findings showed that all instruments were valid and reliable, while the regression model met the assumptions of normality, multicollinearity, and heteroscedasticity. The school environment (β = 0.478, p < 0.001) and community environment (β = 0.263, p = 0.023) were significantly associated with learning achievement, whereas the family environment, despite showing a positive coefficient (β = 0.179), was not statistically significant (p = 0.074). Collectively, the three environments significantly explained students' learning achievement (F = 29.062, p < 0.001; R² = 0.581). These findings indicate that school and community environments demonstrate stronger associations with learning achievement than the family environment in this context. The study underscores the importance of integrating multiple educational environments to better support elementary students' academic achievement.